Impact of forest fire severity on soil physical and chemical properties in pine and scrub forests in high Andean zones of Peru. - Gonzáles, H. (2024)
Forest fires are the main threat to ecosystems and human life. The frequency, seasonality, extent and severity of fires affect ecosystems and the physical and chemical properties of the soil by direct (heating) and indirect (ash) effects. This could affect biodiversity and forest residency in the face of climate change. In this study, we evaluated the impact of fire severity on soil physical and chemical properties caused by forest fires in a high Andean area of Peru. For this purpose, the severity levels, the degree of hydrophobicity, and the physical and chemical properties of the soil were analyzed by sampling in affected areas (Pinus radiata D. Don plantation and shrubland) and unaffected areas. The results showed a very low severity in soil components, with a strong hydrophobicity, more persistent in the forest plantation area than in the shrubland. The physical properties of the soil did not show variations; however, in the Pinus plantations they showed variations in their chemical properties such as pH, electrical conductivity, organic matter, nitrogen and cation exchange capacity compared to areas not affected by the forest fires. Likewise, in the study area an adequate regeneration process was evidenced; in fact, it is important to apply mechanisms to accelerate the restoration of the vegetation cover and the physical and chemical quality of the vegetation.